2010
DOI: 10.1007/s12603-010-0077-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 deficiency in African American and white octogenarians and centenarians in Georgia

Abstract: Objective-Test the hypotheses that vitamin B12 deficiency would be prevalent in octogenarians and centenarians and associated with age, gender, race/ethnicity, living arrangements (community or skilled nursing facility), animal food intake, B-vitamin supplement use, atrophic gastritis, folate status, and hematological indicators.Design-Population-based multi-ethnic sample of adults aged 80 to 89 and 98 and above. Setting-Northern Georgia in the United States.Participants-Men and women aged 80 to 89 (octogenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 31 publications
4
13
1
1
Order By: Relevance
“…Direct comparison of our findings with other studies is hampered by the lack of international consensus as to which nutritional biomarker (biochemical and/or functional), which assay methodology, and which cut off point should be used to define a subclinical micronutrient deficiency in older adults [23,37]. Nevertheless, our population-based data is in line with previous studies that have suggested that subclinical vitamin D and B 12 deficiencies are prevalent public health problems among older adults [12,15,[38][39][40][41][42].…”
Section: Prevalence Of Subclinical Micronutrient Deficiencysupporting
confidence: 75%
“…Direct comparison of our findings with other studies is hampered by the lack of international consensus as to which nutritional biomarker (biochemical and/or functional), which assay methodology, and which cut off point should be used to define a subclinical micronutrient deficiency in older adults [23,37]. Nevertheless, our population-based data is in line with previous studies that have suggested that subclinical vitamin D and B 12 deficiencies are prevalent public health problems among older adults [12,15,[38][39][40][41][42].…”
Section: Prevalence Of Subclinical Micronutrient Deficiencysupporting
confidence: 75%
“…Iron and transferrin saturation showed predicted relationships (17). Similarly, vitamin B12 levels were associated with ethnicity and insulin resistance (likely secondary to use of metformin) (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed serum vitamin B-12 concentrations to determine the sufficiency using cutoff values of ,148 pmol/L (21-24), 200 pmol/L (25)(26)(27), and 258 pmol/L (7,28,29). We also used vitamin B-12 status based on the cutoffs that Stabler et al (30) originally proposed and that we modified for this analysis.…”
Section: Biochemical Methodsmentioning
confidence: 99%
“…For this analysis, we added an additional cutoff of .296 pmol/L (.400 pg/mL) to the original Stabler et al criteria (30). We classified elevated MMA using 2 concentrations: .376 nmol/L (31)(32)(33)(34)(35) and .271 nmol/L (24,28,32,(36)(37)(38)(39). We also examined 4 categories of MMA based on the above cutoffs (.376 and .271 nmol/L) and .210 nmol/L (14,23,40,41).…”
Section: Biochemical Methodsmentioning
confidence: 99%